Optimization of methane production process from synthetic glucose feed in a multi-stage anaerobic bioreactor. Issue 60 (25th December 2016) - Shahperi, Rafidah; Din, Mohd Fadhil Md.; Chelliapan, Shreeshivadasan; Aris, Maizatul Asnie Md.; Selvam, Sivathass Bannir; Abdullah, Norhayati; Yuzir, Muhamad Ali Muhammad
Abstract: The biological conversion of biomass into methane during anaerobic digestion has been studied by many researchers in recent years. In this study, optimization of methane composition during chemical oxygen demand removal was observed in a multi-stage Anaerobic Bioreactor. Synthetic glucose was used as a feed substrate, and the reactor was operated at a hydraulic retention time (HRT) of 1–4 d. Complementary experimental and theoretical test procedures were evaluated for methane optimization. The theoretical methane was recorded as 50.13, 50.02, 50.16, and 50.22% for an HRT of 4, 3, 2, and 1 d, respectively. However, the quantity of methane determined experimentally was significantly lower than the theoretical predictions; this was likely due to the microorganism activity in the reactor that may have interfered with the efficiency of the biogas generation. Experimental data showed a decrease in the methane composition (35.4, 21.2, 19.8, and 18.4% for HRT of 4, 3, 2, and 1 d, respectively) in the reactor system. Thus, the theoretical formula and experimental data together provide an alternative method for the evaluation of bioenergy potential in anaerobic digestion.